PENGARUH NAUNGAN DAN PUPUK KANDANG AYAM TERHADAP PERTUMBUHAN DAN HASIL SUPAN-SUPAN (Neptunia oleracea Lour.) - M. Laily Qadry Sukmana; Hilda Susanti; Gusti Rusmayadi (EnviroScienteae, 2021)
Water Mimosa is an endemic wetland plant that has the potential to be developed due to its high benefits. Water Mimosa commonly grows on the surface of the water and shades under the canopy of other plants. Moreover, Water Mimosa can grow optimally in wetlands rich in N. Chicken manure has the highest N nutrient source compared to other manure. Therefore, it is important to research the effect of shading level and chicken manure dose on the growth and yield of Water Mimosa. The experiment was conducted from January to February 2020 in Sungai Tiung Village, Banjarbaru, using a split-plot, completely randomized design with three replications. The main plot was the shading, consisting of without shading, one layer of 50% shading net, and two layers of 50% shading net. Subplots were doses of chicken manure, namely 0, 5, 10, and 15 ton ha-1. The results indicated that the interaction of various shade levels affected the growth and yield of water mimosa with the optimum value found in the treatment without shade and the dose of chicken manure of 5 tons ha-1.